Rancang Bangun Platform Penjualan Domain Dan Hosting Berbantuan Whmcs Berbasis Web - Fahmi, Rizal; Imilda; Salam, Abdus (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This research discusses the design and development of a web-based domain and hosting sales platform assisted by WHMCS. This platform is designed to make it easier for users to buy and manage their domains and hosting. This platform also provides various useful features for users, such as: domain registration, hosting purchase, account management and help and support. This platform was built using modern web technologies, such as PHP, MySQL, and Bootstrap. WHMCS is used as a billing and customer management platform. The platform is tested using various methods, such as unit testing, integration testing, and functional testing. The results of this research show that the web-based domain and hosting sales platform assisted by WHMCS can provide an easy and effective solution for users to purchase and manage their domains and hosting.